DINAMIKA KELUARGA MADRIGAL DALAM FILM “ENCANTO” ANALISIS KAJIAN TEORI SISTEM KELUARGA - Mawardi, Mawardi; Erawati, Muna; Saadati, Sania (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
Family relationships can be incredibly complex and differ from family to family.Encanto is an animated musical film from Disney that takes us to a magical village in the mountains of Colombia. This village, known as Encanto, is where each member of the Madrigal family has a unique power. However, there is one who does not, and that is Mirabel. This makes her feel different and not fully accepted by her family. The purpose of this study is to find out and understand how the dynamics that exist in the Madrigal family's Encanto movie.In this study, a qualitative descriptive method was used. The choice of this method is based on the focus of the research which aims to analyze the emotional aspects depicted in the characters in the film “Encanto”. Data collection techniques with literature study and documentation. Data Processing and Analysis Techniques with Narrative Analysis which analyzes the storyline, conflict, and resolution in the film. Family Systems Theory views the family as an interrelated system. Changes to one part of the system will impact the other parts. In the context of Encanto, this theory helps us understand that the problem Mirabel faces is not just an individual problem, but rather a problem that involves the entire Madrigal family.The movie actually presents many messages and themes that are very relevant to life.